2004
DOI: 10.1021/ic049559g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of a High Relaxivity Manganese(II)-Based MRI Contrast Agent

Abstract: The manganese(II) ion has many favorable properties that lead to its potential use as an MRI contrast agent: high spin number, long electronic relaxation time, labile water exchange. The present work describes the design, synthesis, and evaluation of a novel Mn(II) complex (MnL1) based on EDTA and also contains a moiety that noncovalently binds the complex to serum albumin, the same moiety used in the gadolinium based contrast agent MS-325. Ultrafiltration albumin binding measurements (0.1 mM, pH 7.4, 37 degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
168
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(180 citation statements)
references
References 61 publications
7
168
0
Order By: Relevance
“…However this latter calculation might overestimate the q value, as it did not take into account the possible contribution of second sphere relaxation. ) which has q = 1 and a negligible second sphere relaxation contribution [29,30]. Taking into account the significant second-sphere contribution expected, our results for MnL 1 point to a q value between 1 and 0.…”
Section: Proton Relaxivitiessupporting
confidence: 53%
“…However this latter calculation might overestimate the q value, as it did not take into account the possible contribution of second sphere relaxation. ) which has q = 1 and a negligible second sphere relaxation contribution [29,30]. Taking into account the significant second-sphere contribution expected, our results for MnL 1 point to a q value between 1 and 0.…”
Section: Proton Relaxivitiessupporting
confidence: 53%
“…Interestingly, the Mn(II)-EDTA-like complex bearing the same recognition synthon displays, again, a high affinity for HSA. It has been reported that in clinical concentrations, about 98% of this agent is bound to serum proteins (67).…”
Section: Magnetic Resonance Imaging Contrast Agents Designed For Hsa mentioning
confidence: 99%
“…The relaxivity was also measured as a function of the proton Larmor frequencies (from 0.01 to 70 MHz) and the experimental data are reported in Figure 1 (left). 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 As such theories have some limitations to properly model the behaviour of slowly tumbling systems at low Larmor frequencies, 30 NMRD data were analysed only in the high-frequency region (> 5 MHz).…”
Section: Preparation and Characterization Of The Mixed Micellesmentioning
confidence: 99%